2010
DOI: 10.1027/1866-5888/a000017
|View full text |Cite
|
Sign up to set email alerts
|

Shared Leadership in Teams

Abstract: Shared leadership is an emergent team process defined by the distribution of leadership functions among multiple team members. Past empirical research on shared leadership has operationalized it as the overall quantity of leadership in the team, neglecting the essence of the conceptual definition – the distribution of leadership. In order to align the conceptual definition with an operational one, we examined shared leadership as network centralization using social network analysis. Using this operational defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(49 citation statements)
references
References 39 publications
1
46
1
1
Order By: Relevance
“…Therefore, if the conditions are suitable for leadership to emerge, a higher level shared leadership would be observed in the later stages of team development. A longitudinal analysis by Small and Rentsch (2010) revealed that shared leadership increased over time. In their study, students formed teams to complete a semester-long business simulation during which eight quarters of simulated business was conducted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if the conditions are suitable for leadership to emerge, a higher level shared leadership would be observed in the later stages of team development. A longitudinal analysis by Small and Rentsch (2010) revealed that shared leadership increased over time. In their study, students formed teams to complete a semester-long business simulation during which eight quarters of simulated business was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…To eliminate the possible effect of vertical leadership on team creativity, the current study did not assign vertical leadership in the teams, following other researchers in the field (e.g., Small and Rentsch, 2010). In this way, we could focus on the function of shared leadership on team creativity and on the underline mechanism of the function.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Moreover, the dimensions cover a broad variety of leadership behaviors, including long-term recognizable task-and relationorientation, as well as behavior especially relevant to modern work life, change-oriented leadership, and networking activities. Collectively, these behaviors go beyond those described in specific leadership theories, such as the theory on transformational leadership (Small & Rentsch, 2010). Therefore, we decided to include shared task, relation, change, and micropolitical leadership orientation as four shared leadership dimensions into SPLIT.…”
Section: Study 1: Scale Development Item Selection and Exploration mentioning
confidence: 99%
“…However, more recently researchers began to investigate "an emer-gent team property that results from the distribution of leadership influence across multiple team members" (Hoch, Pearce, & Welzel, 2010b: p. 105). This dynamic process, described as "shared leadership" in the literature (e.g., Pearce & Sims, 2002;Wang, Waldmann, & Zhan, 2014), is seen as a new form of management (Pearce & Manz, 2005) especially fit to encounter the increasing complexity of working life in which a single leader is unable to effectively perform all important leadership functions (Small & Rentsch, 2010). Shared leadership is not intended to replace vertical leadership (Hoch et al, 2010b;Pearce & Sims, 2002) but to enhance teamwork effectiveness (Ensley, Hmieleski, & Pearce, 2006;Carson, Tesluk, & Marrone, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation